2013
DOI: 10.4103/1319-3767.121032
|View full text |Cite
|
Sign up to set email alerts
|

Oral conditions associated with Hepatitis C virus infection

Abstract: Hepatitis C virus (HCV) infection in more than 170 million chronically infected patients with no developed preventive vaccine is a globally important issue. In addition to expected hepatic manifestations, a number of extrahepatic manifestations, such as mixed cryoglobulinemia, glomerulonephritis, polyarteritis nodosa, rashes, renal disease, neuropathy, and lymphoma, have been reported following HCV infection, which are believed to be influenced by the virus or the host immune response. HCV combination therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 59 publications
(86 reference statements)
0
18
0
1
Order By: Relevance
“…Hepatitis C is generally asymptomatic with up to 80% of infected cases which will progress to persistent infection. About 15-20% of chronic HCV infection progressed to cirrhosis and 1 to 4% are found to be an annual risk of developing hepatocellular carcinoma within 20-30 years [1][2][3]. Blood, blood-products and intravenous drug abuse (IV) are related with the transmission of this virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis C is generally asymptomatic with up to 80% of infected cases which will progress to persistent infection. About 15-20% of chronic HCV infection progressed to cirrhosis and 1 to 4% are found to be an annual risk of developing hepatocellular carcinoma within 20-30 years [1][2][3]. Blood, blood-products and intravenous drug abuse (IV) are related with the transmission of this virus.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Nokhodian and his colleagues (2012) stated that HCV transmission may also be acquired through non-parenteral and non-sexual routes [6]. Indeed, several authors estimated that up to 40% of patients infected with HCV may have non identifiable routes of viral acquisition [3,7,8]. Therefore, identification and elimination of other possible transmission routes will play a significant role in HCV infection restriction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies address the impact of HCV infection in the oral health. These studies highlight the dental diseases associated with both HCV-infection and its extrahepatic manifestations (EHMs) 39 Coates et al, studied the oral health state of HCVinfected persons based on the DMFT index (Decayed, Missing, Filled Teeth index). They found that, patients with chronic HCV infection had more significant dental pathological changes in teeth with carious lesions, expressed a larger number of missing teeth and less dental fillings as compared with the control 40 Moreover, using the CPITN index (Community Periodontal Index of Treatment Needs), HCV patients had more gingival bleeding and deeper periodontal pockets.…”
Section: Oral Diseases Related To Hepatitis C Virus Infectionmentioning
confidence: 99%
“…Some extrahepatic manifestations of HCV infection such as Sjögren syndrome and oral lichen planus can also impact the status of the oral cavity [62,63]. In Sjögren syndrome, the secretion ability of the lachrymal and salivary glands is impaired.…”
Section: Chronic Hepatitis C Infection From An Oral Health Perspectivementioning
confidence: 99%